Farm mechanization and factors affecting its adoption among wheat growing farmers in Rupandehi, Nepal - Ranabhat, Samikshya; Bastola, Arjun; Shrestha, Asmita; Tiwari, Narayan (Nepal Agriculture Research Journal, 2025)
This research aims to discover the factors that affect the adoption of machineries in wheat (Triticum aestivum) growing fields of Rupandehi district. There is very little indication of increased rate of mechanization and dissemination of information is low around the study area. The survey was conducted among 120 wheat growing farmers to determine mechanization practices, adoption scenario as well as constraints encountered during the adoption of mechanization. The primary information was collected through the household survey by asking pre-prepared questionnaire while secondary information was collected through relevant publications. The collected data was processed and analyzed using SPSS, Stata and Ms-Excel, preferential ranking was used to rank the constraints while factors influencing the adoption of new technology during wheat cultivation was analyzed using Stata. The findings show that mechanization during land preparation was highest with the use of cultivator (87.5%) and rotavator (85.8%) but latest technology like super-seeder showed low adoption (12.5%). Similarly, harvesting of wheat was done by combine-harvester (70.8%) and thresher (29.2%). The key constraints identified during adoption of mechanization were unavailability of machineries on time followed by labour shortage. Those factors significantly associated with increment of adoption of new technology were land area under wheat, distance from highway, participation in trainings, involvement in cooperatives and status of land fragmentation. Thus, the study concludes that ensuring availability of machineries and providing trainings on the use of machineries can enhance mechanization among wheat growing farmers ensuring food security in the district.